Overexpression of Bcl-2 inhibits alveolar cell apoptosis during involution and accelerates c-myc-induced tumorigenesis of the mammary gland in transgenic mice - Jäger, Richard; Herzer, Ute; Schenkel, Johannes; Weiher, Hans (Oncogene, 1997)
Expression of the apoptosis-inhibitory protein Bcl-2 has frequently been detected in human cancer including mammary carcinoma. The functional significance of its expression has been well established in experimental tumors of the lymphoid system, however, remains to be elucidated for epithelial tumors. In order to assess the role of Bcl-2 in mammary tumorigenesis we have generated WAP-bcl-2 transgenic mice. The strong overexpression of Bcl-2 in lactating mammary glands was preserved during early postlactational involution and apoptosis of alveolar epithelial cells was prevented without influencing the dedifferentiation of the milk-producing epithelium. Although Bcl-2 overexpression was not sufficient to induce spontaneous tumors it, however, led to an accelerated development of MMTVmyc transgene-induced mammary tumors. In the mammary glands of MMTVmyc transgenic mice, a high proportion of apoptotic cells was detected which was significantly reduced in the mammary glands of WAP-bcl-2/MMTVmyc double transgenic mice. Taken together, these results suggest that Bcl-2 contributes to mammary tumorigenesis by inhibiting apoptosis.
Im Text ist "myc" kursiv gedruckt
Gesehen am 07.10.2020